The Right Tools for the Job: Cooperative Breeding Theory and an Evaluation of the Methodological Approaches to Understanding the Evolution and Maintenance of Sociality - Hing, Martin L.; Klanten, O. Selma; Dowton, Mark; Wong, Marian Y. L. (Frontiers in Ecology and Evolution, 2017)
Why do we observe so many examples in nature in which individuals routinely delay or completely forgo their own reproductive opportunities in order to join and remain within a group? Cooperative breeding theory provides a rich framework with which to study the factors that may influence the costs and benefits of remaining philopatric as a non-breeder. This is often viewed as an initial step in the development of costly helping behavior provided by non-breeding subordinates. Despite many excellent empirical studies testing key concepts of the theory, there is still debate regarding the relative importance of various evolutionary forces, suggesting that there may not be a general explanation but rather a dynamic and taxonomically varied combination of factors influencing the evolution and maintenance of sociality. Here, we explore two potential improvements in the study of sociality that could aid in the progress of this field. The first addresses the fact that empirical studies of social evolution are typically conducted using either comparative, observational or manipulative methodologies. Instead, we suggest a holistic approach, whereby observational and experimental studies are designed with the explicit view of advancing comparative analyses of sociality for the taxon, and in tandem, where comparative work informs targeted research effort on specific (usually understudied) species within the lineage. A second improvement relates to the broadening of tests of cooperative breeding theory to include taxa where subordinates do not necessarily provide active cooperation within the group. The original bias towards ‘helpful subordinates’ arose from a focus on terrestrial taxa. However, recent consideration of other taxa, especially marine taxa, is slowly revealing that the theory can and should encompass a continuum of cooperative social systems, including those where subordinates do not actively help. This review summarizes the major hypotheses of cooperative breeding theory, one of the dominant frameworks to examine social evolution, and highlights the potential benefits that a combined methodological approach and a broader application could provide to the study of sociality.